Development of Relaxin-3 Agonists and Antagonists Based on Grafted Disulfide-Stabilized Scaffolds - Lee, Han Siean; Postan, Michael; Song, Angela; Clark, Richard J.; Bathgate, Ross A. D.; Haugaard-Kedström, Linda M.; Rosengren, K. Johan (Frontiers in Chemistry, 2020)
Relaxin-3 is a neuropeptide with important roles in metabolism, arousal, learning and memory. Its cognate receptor is the relaxin family peptide-3 (RXFP3) receptor. Relaxin-3 agonist and antagonist analogues have been shown to be able to modulate food intake in rodent models. The relaxin-3 B-chain is sufficient for receptor interactions, however, in the absence of a structural support, linear relaxin-3 B-chain analogues are rapidly degraded and thus unsuitable as drug leads. In this study, two different disulfide-stabilised scaffolds were used for grafting of important relaxin-3 B-chain residues to improve structure and stability. The use of both Veronica hederifolia Trypsin inhibitor (VhTI) and apamin grafting resulted in agonist and antagonist analogues with improved helicity. VhTI grafted peptides showed poor binding and low potency at RXFP3, on the other hand, apamin variants retained significant activity. These variants also showed improved half-life in serum from ~5 min to >6 h, and thus are promising RXFP3 specific pharmacological tools and drug leads for neuropharmacological diseases.